Stewardship behavior and creativity - Volker G. Kuppelwieser (Management Revue, 2011)
Despite the importance and popularity of the stewardship concept in the current management literature, antecedents and the role of the surrounding framework of stewardship remains poorly understood. Similarly, relatively little is known about the outcomes of stewardship. In this study I set out to examine 1) how relational, motivational, and contextual support influences the establishment of stewardship and 2) what the role of managerial stewardship is in employee creativity. Drawing on a sample of 191 senior and middle managers, I demonstrate that relational and motivational support have a positive influence and contextual support has no influence on stewardship. Additionally I confirm that managerial stewardship has a positive relationship with employees' creativity.
Keywords: M00; M10; M14; 650; agency theory; creativity; leadership; stewardship